NLP-based faceted search: Experience in the development of a science and technology search engine - Armentano, Marcelo Gabriel (2014)
An appropriate promotion, distribution and dissemination of scientific, artistic and technology developments can foster the collaboration between a country’s productive and academic sectors. The purpose of this paper is to present a novel search engine aiming at helping people to access science and technology advances, researchers and institutions working in specific areas of research. Our search engine first collects information disseminated on the Web in academic institution sites and in researchers personal homepages. Then, after intensive text processing, it summarizes the information in an enriched and user-friendly presentation oriented to non-expert users. Stable performance and an acceptable level of effectiveness for automatic named entities recognition indicate the potential of our approach for bridging the gap between the heterogeneous and unstructured information available on the Web about the research and development advances in a country and the innovation required by the productive sectors.